2002
DOI: 10.1210/en.2002-220385
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth/Permeability Factor by Endometrial Glandular Epithelial and Stromal Cells in Baboons during the Menstrual Cycle and after Ovariectomy

Abstract: Vascular endothelial growth/permeability factor (VEG/PF) has a crucial role in angiogenesis, and neovascularization is essential in preparing the uterine endometrium for implantation. However, the regulation of VEG/PF synthesis by particular cell types of the endometrium during the human menstrual cycle is not well understood. Therefore, in the present study the baboon was used as a nonhuman primate to determine the role of the ovary in vivo in endometrial VEG/PF expression. VEG/PF mRNA levels were quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Both in vitro and in vivo studies have proved that androgen could up-regulate VEGF expression (34,35), whereas androgen ablation inhibited VEGF expression (36). On the contrary, estrogen reduced VEGF expression (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have proved that androgen could up-regulate VEGF expression (34,35), whereas androgen ablation inhibited VEGF expression (36). On the contrary, estrogen reduced VEGF expression (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have now shown that the different VEGFA isoforms are present in the endometrium (Charnock-Jones et al 1993, Halder et al 2000, Sharkey et al 2000, Ancelin et al 2002, Niklaus et al 2002, Sugino et al 2002. As in other tissues, VEGFA 164 is believed to be the dominant isoform in human endometrium.…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 99%
“…In some species, VEGF is expressed in placentomes [153]. VEGF is partly regulated by hormones during the cycle as well as chorionic gonadotropin at implantation and [146,147,[153][154][155][156][157]. Indeed mefipristone down-regulates local VEGF production [158], whereas, conversely, HLA-G (a non polymorphic Class I HLA antigen present on extravillous human trophoblasts), while inhibiting NK cell mediated cytotoxicity [2,122,[159][160][161], up-regulates VEGF production by uNK cells [162], a property fitting with a role of HLA-G in angiogenesis [163].…”
Section: The Role Of the Immune System On Local Vascularizationmentioning
confidence: 99%